Review of the Fund's Income Position for FY 2011 and FY 2012. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper reviews the Fund's income position for FY 2011 and FY 2012. The paper updates projections provided at the FY 2011 midyear review and sets out related proposed decisions for the current and next financial years. A companion paper provides an update on the consolidated medium-term income and expenditure framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Commitment Fee; Financial Year; Income; PP; Special Drawing Rights; United States